Fabricato: from the capital streategy to the streategy of the capital (1991)
During the decade of the 80 a depresive cycle of the world's economy was presented and affected remarkably the colombian industrial big export companies. The concordats were generalized up to the point where it was stated that the economy was concord. This article presents the case of FABRICATO S.A. COMP ANY were the management of the crisis, teachesinnovational strategies, to deal at companies with difficulties, showing, positive results after saving it from going bankrupt. This company dealt the game of factors under the logic of the financial capital. The variables which they deal with were: minimizing the personnel (-2580 workers) and the weages with a big social consecuence upon the Aburra' s Valley population; dealing with the trade unions conflict in order to the union' s partícipation at the concordating board; emitting and massive selling shares to the open market, prooving the comunityes solidarity with a company with a great deal of upon Antioquias's population. Incorporation of techonological innovation in order to make it competitive with the textil industry once again; adaptation to the demands of the fashion market. Understanding the strategy to reduce the velocity in the rotation of accounts to be paid which is the inmediate effect in any concordat declaration. The positive management of the lastyears the company has not being able to be on the level of the exportations after of the crisis.